Metal trap, method for producing metal trap, and fluid catalytic cracking catalyst composition
A silicon oxide-alumina-magnesium oxide metal scavenger is developed to address the challenge of vanadium poisoning in fluid catalytic cracking catalysts, achieving effective vanadium trapping, catalyst stabilization, and enhanced abrasion resistance.
Patent Information
- Application Number
- JP2021096757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-09
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-06-09
AI Technical Summary
Fluid catalytic cracking catalysts used in hydrocarbon oil processing are susceptible to poisoning by vanadium, leading to catalyst deterioration and reduced activity, with existing solutions offering limited effectiveness in suppressing deterioration and maintaining high abrasion resistance.
A metal scavenger composed of a silicon oxide binder, an alumina component, and a Group 2 element oxide, specifically magnesium oxide, is developed. This scavenger is designed to trap vanadium, prevent catalyst deterioration, and enhance wear resistance by optimizing specific surface area, pore volume, and ignition weight reduction.
The metal scavenger effectively traps vanadium, suppresses catalyst deterioration, and maintains high abrasion resistance, thereby improving the longevity and performance of fluid catalytic cracking catalysts in hydrocarbon oil processing.
Smart Images

Figure 0007665429000003 
Figure 0007665429000001 
Figure 0007665429000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a technical field of capturing and immobilizing vanadium, which is one of the poisoning elements of fluid catalytic cracking catalysts, in the catalytic cracking reaction process. [Background technology]
[0002] With the increase in the ratio of residual oil processed at refineries, there is an urgent need to develop and improve catalysts for fluid catalytic cracking catalysts (RFCC) used for residual oil processing. One of the problems with RFCC is that the concentration of catalyst poisoning metals (Ni, V) contained in crude oil (or residual oil) is high, which causes great damage to the catalyst. Measures to mitigate this effect include adding elements that have a good affinity with the poisoning metals (poisoning metal scavengers) to the fluid catalytic cracking catalyst (FCC) and blending a certain amount of promoter (additive) containing a high concentration of an element with a good affinity into the FCC catalyst. These measures are based on the idea of capturing the poisoning metals as a certain crystalline phase and mitigating the adverse effects on catalytic activity.
[0003] For example, vanadium present as an impurity in the feedstock oil is known to form vanadic acid in the atmosphere inside a regeneration tower for regenerating a fluid catalytic cracking catalyst, which causes crystal destruction and activity reduction of the zeolite in the fluid catalytic cracking catalyst. For this reason, a method of incorporating a component capable of capturing vanadium into the fluid catalytic cracking catalyst or a method of mixing the above-mentioned component as an additive with the base catalyst have been adopted.
[0004] Patent Document 1 discloses an additive comprising free magnesium oxide and a magnesium silicate cement binder produced in situ as an additive for passivating vanadium when added to a fluid catalytic cracking catalyst, and a method for producing the additive. This additive has a low surface area and minimal cracking activity.
[0005] Furthermore, Patent Document 2 discloses dry particles made of kaolin, magnesium oxide or magnesium hydroxide, and calcium carbonate, containing at least 10 wt % magnesium oxide, as metal capture particles used for metal passivation during fluid catalytic cracking.
[0006] Patent Document 3 discloses a metal capture agent that is composed of a binder mainly containing silicon oxide, one or two selected from an alumina component and a clay mineral, and a compound of a Group 2 element as a first metal component, and that has a wear resistance index CAI within a predetermined range. Furthermore, this metal capture agent has a feature that no peak of a silicate of the first metal component is detected in an X-ray diffraction analysis. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 08-504397 [Patent Document 2] Special Publication No. 2013-506548 [Patent Document 3] International Publication No. 2020 / 129455 [Non-patent literature]
[0008] [Non-Patent Document 1] Catalyst Chemical Technical Journal Vol.13, No.1, P65, 1996 Summary of the Invention [Problem to be solved by the invention]
[0009] The inventors developed the metal capture agent disclosed in Patent Document 3 and developed a fluid catalytic cracking catalyst containing the metal capture agent. However, there was a need for a metal capture agent that can suppress deterioration of the fluid catalytic cracking catalyst and has excellent wear resistance. Therefore, an object of the present invention is to provide a metal capture agent capable of capturing and immobilizing vanadium, which is one of the poisoning elements of a fluid catalytic cracking catalyst used in the catalytic cracking reaction process of hydrocarbon oils, thereby suppressing deterioration of the fluid catalytic cracking catalyst, and also capable of maintaining high catalytic activity while being highly resistant to wear, and a method for producing the same. Another object of the present invention is to provide a fluid catalytic cracking catalyst composition containing the metal capture agent. [Means for solving the problem]
[0010] Against this technical background, the inventors conducted intensive research to solve the above problems, and as a result, discovered that by dispersing an oxide of a Group 2 element in a silicon oxide binder and an alumina component, a metal capture agent that is highly resistant to wear and that suppresses deterioration of a fluid catalytic cracking catalyst can be obtained, and thus developed the present invention.
[0011] The present invention, which has been developed to solve the above problems and achieve the above objects, is as follows: First, the present invention provides a metal capture agent that is characterized by comprising a silicon oxide binder, an alumina component, and an oxide of a Group 2 element as a metal component, and by using magnesium oxide having a specific specific surface area as the oxide of the Group 2 element, the metal capture agent having a wear resistance in the range of 0.1 to 10 and a loss on ignition (LOI) in the range of 20 to 35.
[0012] The metal capture agent according to the present invention is a metal capture agent containing a silicon oxide (silica-based) binder, an alumina component, and a metal component, (a) the content of the silicon oxide (silica-based) binder is 15 to 35 mass% in terms of oxide relative to the metal capture agent; (b) the content of the alumina component is 10 to 30 mass% in terms of oxide relative to the metal capture agent, (c) the average particle size of the metal capture agent is in the range of 40 to 100 μm and the specific surface area is in the range of 130 to 280 m 2 / g and a pore volume in the range of 0.05 to 0.50 ml / g.
[0013] The metal capture agent according to the present invention is (1) The metal capture agent has a wear resistance index (CAI) in the range of 0.1 to 10; (2) The content of the metal component is 20 to 80 mass % in terms of oxide relative to the metal capture agent; (3) The metal capture agent further contains an alkali metal M, and the content of the alkali metal M is 1.5 mass% or less in terms of oxide MO. (4) It is believed that a more preferable solution is that the above metal capture agent has a loss on ignition (LOI) in the range of 20 to 35.
[0014] Secondly, the present invention provides a method for producing any one of the above-mentioned metal capture agents, which includes a first step of adding an alumina component or an alumina component precursor to a silicon oxide (silica-based) binder, mixing the silicon oxide (silica-based) binder with the alumina component or the alumina component precursor, further mixing a compound of a metal component, and heating the mixed slurry containing the metal component to obtain a metal capture agent precursor; a second step of drying the metal capture agent precursor to obtain spray-dried particles of the metal capture agent precursor (metal capture agent); a third step of washing the spray-dried particles (metal capture agent) to obtain a spray-dried particle washed cake; and a fourth step of heat-treating the washed cake of the spray-dried particles.
[0015] The method for producing the metal capture agent according to the present invention is as follows: (5) the heat treatment of the washed cake of spray-dried particles comprises applying hot air at 80 to 200°C to the washed cake of spray-dried particles at a temperature increase rate of 2 to 10°C / min to heat the washed cake of spray-dried particles to 80 to 175°C, and recovering the cake; (6) In the first step, the pH of the mixed slurry is adjusted to a range of 10.0 to 13.0. (7) It is considered that a more preferable solution would be to include a step in which, in the third step, the spray-dried particles are washed multiple times and the pH of the suspension slurry in which the spray-dried particles are dispersed in water is adjusted to a range of 10.0 to 12.0.
[0016] Thirdly, the present invention provides a fluid catalytic cracking catalyst composition comprising any one of the above metal capture agents and a fluid catalytic cracking catalyst. Effect of the Invention
[0017] In the present invention, as a metal capture agent, an alumina component is added to a silicon oxide binder, and an oxide of a Group 2 element, which is a metal component having a vanadium capture function, such as magnesium and calcium, is dispersed therein. This improves the wear resistance of the metal capture agent, suppresses deterioration of the fluid catalytic cracking catalyst, and allows each compound used to be used effectively. In addition, by using magnesium oxide having a specific specific surface area as a compound of a Group 2 element, which is a metal component contained in the metal capture agent, the wear resistance of the metal capture agent can be improved and its loss on ignition (LOI) can be set to the range of 15 to 35. Therefore, according to the present invention, the utilization efficiency of each compound can be increased (loss is reduced), and the amount of each compound used can be reduced. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a flow chart showing each production step of a method for producing a metal capture agent according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Preferred embodiments of the present invention will now be described in detail. [Metal Scavenger] The metal capture agent of the present invention is constructed by adding an alumina component to a silicon oxide (silica-based) binder, and dispersing a metal oxide having a vanadium (V) capturing function as the metal component.
[0020] <Silicon oxide (silica-based) binder component> The binder used in the present invention contains silicon oxide (silica-based). The binder may contain Ti oxide in addition to silicon oxide, and the content of Ti oxide is preferably 1 to 20 mass% of the mass of the binder.
[0021] By using silicon oxide as the silica-based binder of the metal capture agent of the present invention, the metal capture agent in which a metal component is dispersed in a silica-based binder has the advantages of being more thermally stable and less prone to phase transition than other metal capture agents in which a metal component is supported on a carrier mainly composed of titanium oxide, and furthermore, having a stronger interaction with a compound having a vanadium (V) capturing function, and making it easier to disperse the metal component on the metal capture agent surface. In addition, the wear resistance of the metal capture agent is improved.
[0022] The silicon oxide (silica-based) is preferably fine particles, and the average particle size of the fine particles is preferably in the range of 4 to 100 nm. If the average particle size is 4 nm or more, it is preferable since it can exist as fine particles. On the other hand, if the average particle size is 100 nm or less, it is preferable since it can maintain its strength as a metal capture agent. More preferably, the average particle size of the silicon oxide (silica-based) fine particles is in the range of 4 to 80 nm, and even more preferably in the range of 4 to 50 nm.
[0023] The average particle size of silicon oxide (silica-based) fine particles was determined by the following method: The specific surface area SA (m 2 / g) was measured, and the average particle size was calculated using the following formula. Average particle diameter (nm)=6000 / {SA(m 2 / g)×ρ(g / cm 3 )} where ρ is the density of silicon oxide (silica-based) particles, 2.2 g / cm 3 It is.
[0024] The content of the silicon oxide (silica-based) binder in the metal capture agent is preferably in the range of 10 to 30 mass% in terms of oxide (SiO2) relative to the metal capture agent. If the silicon oxide (silica-based) binder is less than 10 mass%, the strength of the metal capture agent may not be maintained. On the other hand, if it exceeds 30 mass%, the silicon oxide (silica-based) binder may cover the surface of the oxide or carbonate of the Group 2 element, which may cause a decrease in capture performance and diffusibility as a metal capture agent. More preferably, the silicon oxide (silica-based) content is in the range of 10 to 25 mass%.
[0025] <Alumina component> As the alumina component, aluminum hydroxide, pseudoboehmite (boehmite sol), or basic aluminum chloride is used as an alumina component precursor that generates alumina in the manufacturing process of the metal capture agent of the present invention. Pseudoboehmite (boehmite sol) is preferably selected as the alumina component. The content of the alumina component in the metal capture agent is preferably 10 to 30 mass% in terms of oxide (Al2O3), and more preferably 15 to 25 mass%. The alumina component has the function of maintaining the catalyst shape and wear resistance, and maintaining the pore structure.
[0026] <Metal components> The metal capture agent of the present invention contains an oxide of a Group 2 element as a metal component in a silicon oxide (silica-based) binder. The oxide of the Group 2 element may be added directly to the silicon oxide (silica-based) binder, or may be added as, for example, a hydroxide, a carbonate, an oxalate, or a precursor thereof (hereinafter, referred to as a metal component). When a precursor is added to the silica-based binder, the precursor becomes the desired compound, an oxide of a Group 2 element, by carrying out a heat treatment.
[0027] The metal component contains at least Mg, and preferably contains both Mg and Ca. The content of the metal component in the metal capture agent is preferably 20 to 80 mass% in terms of oxide relative to the metal capture agent. If the content of the metal component is excessively smaller than 20 mass% in terms of oxide, it is not preferable because the metal capture ability required for the reaction with vanadium, which is one of the poisoning elements of the fluid catalytic cracking catalyst, may not be ensured, and if it is excessively larger than 80 mass%, it is not preferable because the metal component is likely to aggregate and may hinder dispersibility. When the metal component contains both Mg and Ca, it is preferable that the content of the metal component Mg in the metal capture agent is 15 to 60 mass% in terms of oxide (MgO) and the content of the metal component Ca is 5 to 20 mass% in terms of oxide (CaO).
[0028] Here, the MgO and CaO used as the metal components are not particularly limited, and may be MgO and CaO themselves, or may be magnesium carbonate, calcium carbonate, or the like, which is subjected to a calcination treatment to obtain an oxide of the second element, which is the desired metal component, regardless of whether the substance is inorganic or organic.
[0029] Furthermore, the specific surface area of MgO used as the metal component is 20 to 40 m 2 / g. The specific surface area of MgO is preferably in the range of 20 m 2 / g or more is preferable because the function as a metal capture agent is not reduced. 2 / g or less is preferable because the viscosity of the mixed slurry obtained by mixing the raw materials of the metal capture agent containing the silicon oxide (silica-based) binder, the alumina component, and the metal component does not increase too much to prevent spray drying.
[0030] <Alkaline metal component> The metal capture agent of the present invention contains an alkali metal (M) such as a sodium type or lithium type. The content of the alkali metal (M) in the metal capture agent is preferably 1.5 mass% or less in terms of M2O oxide. A main catalyst generally contains a zeolite component, and by controlling the content of the alkali metal (M), it is possible to mitigate the effect of the M2O oxide on the zeolite (such as poisoning of the zeolite). Furthermore, it is more preferable that the content of the alkali metal (M) is 1.0 mass% or less in terms of M2O oxide.
[0031] <Physical properties of metal scavengers> (CCIC Attrition Index, CAI) The attrition resistance of the metal capture agent according to the present invention is measured by the attrition resistance index (CCIC Attrition Index, CAI) measured by the method described in Non-Patent Document 1. Here, the attrition resistance index CAI of the metal capture agent must be in the range of 0.1 to 10. If it is less than 0.1, the metal capture component may not be used effectively, while if it exceeds 10, the metal capture agent may be powdered during use, which may cause equipment trouble or powder contamination of the product. Furthermore, it is more preferable that the CAI is in the range of 0.2 to 6.
[0032] (Average particle size) The metal capture agent of the present invention preferably has an average particle size in the range of 40 to 100 μm. The particle size was evaluated by measuring by a dry micromesh sieve method, and the 50% by mass value (D50) was taken as the average particle size. If the average particle size is too small than 40 μm, the metal capture efficiency decreases, while if it is too large than 100 μm, the wear resistance and strength of the metal capture agent may decrease. Furthermore, it is more preferable that the average particle size of the metal capture agent is in the range of 50 to 90 μm.
[0033] (Specific surface area (SA)) The metal capture agent of the present invention has a specific surface area (SA) measured by the BET method of 130 to 280 m 2 / g. The specific surface area of the metal capture agent is preferably in the range of 130 m 2 If the specific surface area of the metal capture agent is too small, the compounds contained in the metal component tend to aggregate, and the metal capture efficiency decreases. 2 If the specific surface area is excessively larger than 140 to 250 m / g, the strength of the metal capture agent may be reduced, and the shape retention of the metal capture agent may be reduced. 2 It is more preferable that the range is / g.
[0034] (Pore volume (PV)) The metal capture agent of the present invention preferably has a pore volume (PV) measured by a water pore filling method in the range of 0.05 to 0.50 ml / g. If the pore volume (PV) of the metal capture agent is too small compared to 0.05 ml / g, the metal capture efficiency decreases, while if it is too large compared to 0.50 ml / g, the catalyst may not have sufficient strength. Furthermore, the pore volume (PV) of the metal capture agent is more preferably in the range of 0.05 to 0.45 ml / g, and even more preferably in the range of 0.05 to 0.40 ml / g. The pore volume refers to the volume of pores having a pore diameter of 41 Å (4.1 nm) or more.
[0035] (Bulk density (ABD)) The bulk density (ABD) of the metal capture agent according to the present invention is preferably 0.70 g / ml or more. The bulk density of the metal capture agent was measured by using a 25 ml cylinder to measure the weight of the metal capture agent and calculating the bulk density from the weight per unit volume. If the bulk density is lower than 0.70 g / ml, the abrasion resistance is insufficient, and when used as a fluid catalyst, it is easily powdered, which may cause the catalyst to scatter, making it unsuitable for practical use. The upper limit of the bulk density is the density determined by the composition.
[0036] (Loss on ignition (LOI)) The loss on ignition (LOI) of the metal capture agent according to the present invention is preferably in the range of 15% to 35%, and more preferably in the range of 20% to 30%. The LOI was measured by measuring the weight loss when the agent was kept in an electric furnace at 1000°C for 1 hour, and calculating the weight loss rate to obtain the loss on ignition (LOI).
[0037] [Metal capture agent manufacturing method] Fig. 1 is a flow diagram showing each manufacturing step of the manufacturing method of the metal capture agent of the present invention. Each step of the manufacturing method of the metal capture agent of the present invention will be described below. The manufacturing method of the metal capture agent according to the present invention is characterized by including a first step of adding an alumina component or an alumina component precursor to a silicon oxide (silica-based) binder, mixing the silicon oxide (silica-based)-alumina component, further mixing a compound of the metal component, and heating the mixed slurry to which the metal component has been added to obtain a metal capture agent precursor, a second step of drying the metal capture agent precursor to obtain spray-dried particles (metal capture agent), a third step of washing the spray-dried particles (metal capture agent), and a fourth step of heat-treating the washed spray-dried particles. Each step will be described below.
[0038] <First step: Step of obtaining a metal capture agent precursor from a mixed slurry of a silicon oxide (silica-based) binder, an alumina component, and a metal component> In the first step, an alumina component or an alumina component precursor is added to a silicon oxide (silica-based) binder, the silicon oxide (silica-based) and the alumina component are mixed, and further a compound of a metal component is mixed to obtain a mixed slurry with the metal component added. In the first step, the order of addition of each component required to obtain a mixed slurry is not particularly limited, and the order of addition of each component may be changed. In the present invention, a method in which the metal component is added later will be described. Alternatively, a method in which all components are added simultaneously may be used.
[0039] First, a mixed slurry of silicon oxide (silica-based)-alumina components is prepared. The mixed slurry of silicon oxide (silica-based)-alumina components may use, for example, a silicon oxide (silica-based) gel or sol as a silicon oxide (silica-based) binder, and the silicon oxide (silica-based) sol may be obtained by passing an aqueous solution of silicate through an ion exchange resin to remove cations. The silicon oxide (silica-based) gel or sol obtained at this time contains silicon oxide (silica-based) fine particles made of silicon oxide. The average particle size of the silicon oxide (silica-based) fine particles is preferably 4 nm or more (this value is the minimum value at which the mixed slurry of silicon oxide (silica-based)-alumina components can exist as a sol). The average particle size of the silicon oxide (silica-based) fine particles is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less. The silicon oxide (silica-based) fine particles referred to here is a general term for silicon oxide (silica-based) hydrate or silicon oxide (silica-based) slurry obtained by the above-mentioned method. In addition to silicon, a Ti oxide precursor may be added to the silicon oxide (silica-based) fine particles, and these may be added when preparing the silicon oxide (silica-based) binder, so long as the content of these is within the range of 1 to 20 mass% in terms of oxide relative to the silicon oxide (silica-based).
[0040] Next, as the alumina component, for example, pseudo-boehmite is dispersed in pure water to prepare a pseudo-boehmite slurry. This pseudo-boehmite slurry is added to the above mixed slurry of silicon oxide (silica-based) and alumina component to prepare a mixed slurry of silicon oxide (silica-based) and alumina component. As the alumina component, in addition to pseudo-boehmite, aluminum hydroxide, basic aluminum chloride, etc. can be used.
[0041] To the mixed slurry obtained in the above step, an aqueous solution obtained by dissolving a metal component or the metal component is added at the same time to obtain a mixed slurry. After stirring and mixing this mixed slurry, it is heated to obtain a metal capture agent precursor. The mixing conditions are as follows: the mixed slurry is heated and maintained at 20 to 90°C, preferably 25 to 80°C, and an aqueous solution containing a metal component heated to ±5°C, preferably ±2°C, more preferably ±1°C of the temperature of this mixed slurry is added continuously for usually 5 to 20 minutes, preferably 7 to 15 minutes so that the pH becomes 10.0 to 13.0, preferably 10.5 to 11.5, more preferably 10.6 to 11.3, to obtain a metal capture agent precursor.
[0042] The metal component includes an oxide of a Group 2 element. The metal component preferably includes both MgO and CaO. The Mg oxide and Ca oxide used here can be made from compounds such as oxalates, hydroxides, and carbonates. These compounds may be magnesium carbonate or calcium carbonate, which produces Mg oxide or Ca oxide by firing or the like. The average particle size of the oxide of the Group 2 element contained in these metal components is preferably 100 μm or less, and in some cases, it is preferable to use the oxide after pulverization. The specific surface area of MgO used as the metal component here is 20 to 40 m. 2 / g. The specific surface area of MgO is preferably in the range of 20 m 2 / g or more, the specific surface area of the prepared metal capture agent is increased, the performance is improved, and the physical properties are good, which is preferable. The specific surface area of MgO is 40m 2 If the content is less than or equal to 1, the increase in viscosity of the prepared slurry can be suppressed, and a stable production of a metal capture agent can be achieved, which is preferable.
[0043] <Second step: Step of drying the metal capture agent precursor to obtain spray-dried particles> The second step is a step of drying the metal capture agent precursor to obtain spray-dried particles (metal capture agent). The metal capture agent precursor obtained in the first step is dried at a temperature of 100 to 600°C, preferably 110 to 600°C, and more preferably 400 to 600°C, for 0.5 to 10 hours, preferably 1 to 8 hours, to produce the spray-dried particles (metal capture agent) of the present invention. The metal capture agent precursor may be dried by spray drying using a spray dryer. Spray drying is more practical. For this reason, the spray drying conditions are preferably within the following conditions, for example.
[0044] In detail, the spray drying is carried out by filling the mixed slurry containing the metal capture agent precursor obtained in the first step into a slurry storage tank of a spray dryer, and spraying the mixed slurry into a drying chamber through which an airflow (e.g., air) adjusted to a temperature in the range of 120 to 450°C, for example, 230°C, flows. By the spray drying, spray-dried particles (hereinafter, also simply referred to as metal capture agents) are obtained. Although the temperature of the airflow is lowered by the spray drying of the mixed slurry, the initial drying temperature at the outlet of the drying chamber is maintained in the range of 50 to 300°C, for example, 120°C, using a heater or the like. The drying speed can be set to 1.0 to 2.0°C / min for the temperature rise from the initial drying temperature of 120°C to 450°C.
[0045] As described above, in the second step of the method for producing a metal capture agent according to the present invention, a metal capture agent having excellent wear resistance can be obtained by lowering the initial drying temperature of the mixed slurry solution, controlling the temperature rise rate, and performing drying under mild conditions. The spray-dried particles may be pre-dried before the washing described below. Pre-drying may be performed within a temperature range of about 100 to 300°C for 0.5 to 5.0 hours. By performing pre-drying in this manner, it is possible to prevent dissolution of components and collapse of the metal capture agent due to washing in the subsequent stage.
[0046] <Third step: Dispersing the metal capture agent in water to obtain a slurry and washing the slurry> When the spray-dried particles (metal capture agent) obtained in the second step contain by-products, it is preferable to carry out a washing process to remove the by-products. By carrying out the washing process, a spray-dried particle washed cake containing the spray-dried particles (metal capture agent) is obtained. When carrying out the washing process, specifically, washing is carried out with warm water (40 to 80°C) at a solid-liquid ratio of 1:3 to 1:50 and a stirring time of about 3 to 30 minutes. The washing process can reduce the content of the alkali metal M contained in the metal capture agent of the present application. The content of the alkali metal M contained in the metal capture agent of the present application is preferably 1.5 mass% or less in terms of M2O oxide relative to the metal capture agent, and more preferably 1.0 mass% or less. By controlling the content of the alkali metal M, it is possible to alleviate the effect of M2O oxide on the zeolite contained in the main catalyst (poisoning of the zeolite, etc.). Here, examples of the alkali metal M include Na, Li, and K. Furthermore, by repeating the washing step of the spray-dried particles (metal capture agent) or extending the washing time, the specific surface area and abrasion resistance of the metal capture agent can be improved.
[0047] Furthermore, when washing the spray-dried particles, it is preferable to add an alkali metal aqueous solution in which an alkali metal compound such as sodium hydroxide is dissolved in water to obtain a suspension slurry, and adjust the pH of the suspension slurry to a range of 10.0 to 12.0. Furthermore, it is more preferable to adjust the pH of the alkali metal aqueous solution to a range of 10.5 to 11.7. If the pH of this alkali metal aqueous solution is 10.0 or more, vanadium capture components Mg and Ca are not eluted from the metal capture agent, and the wear resistance of the metal capture agent is not reduced, which is preferable. If the pH of this alkali metal aqueous solution is 12.0 or less, the silica source, which is a silicon oxide binder component contained in the metal capture agent, is not eluted, and the wear resistance of the metal capture agent is not reduced, which is preferable. Thereafter, it is preferable to resuspend the spray-dried particle washed cake in ion-exchanged water or the like, dehydrate it, and wash it with water. The slurry temperature during suspension is preferably 40 to 80° C., and the water temperature is preferably 40 to 80° C. Furthermore, by repeating this process, the content of the alkali metal M can be reduced.
[0048] <Fourth step: Step of drying and / or calcining / heating the spray-dried particles (metal capture agent) to obtain a metal capture agent> The metal capture agent of the present invention is obtained by drying and / or calcination heat treatment of the washed spray-dried particles (metal capture agent) obtained in the third step for 0.1 to 10 hours, preferably for 0.2 to 8 hours, at a temperature of 80 to 200° C., preferably 80 to 175° C., and more preferably 80 to 150° C. The washed spray-dried particles (metal capture agent) can be dried by a conventionally known method using a box dryer, a rotary dryer, or the like.
[0049] In detail, the metal capture agent is obtained by introducing the washed cake, which is the spray-dried particles (metal capture agent) obtained in the third step after washing, into a rotary dryer through which an air current (e.g., air) adjusted to a temperature in the range of 80 to 200° C., for example, 120° C. flows. For example, the heat treatment of the washed cake of the metal capture agent is set to 80 to 200° C., and the cake is heated at a heating rate of about 2.0 to 10.0° C. / min until the temperature reaches 80 to 200° C., and the cake is collected as a dry powder.
[0050] [Fluid catalytic cracking catalyst composition] The fluid catalytic cracking catalyst composition of the present invention means a blend of a fluid catalytic cracking catalyst and the metal capture agent of the present invention. The fluid catalytic cracking catalyst composition of the present invention (hereinafter referred to as the "catalyst composition of the present invention") contains at least the above-mentioned metal capture agent, a zeolite component, a binder component (silica-based binder or alumina-based binder), and a clay mineral component. The fluid catalytic cracking process of crude oil or residual oil using the catalyst composition is carried out under high temperature and high pressure conditions in a hydrogen atmosphere by filling the catalyst composition into a fixed bed reactor. As the fluid catalytic cracking catalyst contained in the fluid catalytic cracking catalyst composition of the present invention, a conventionally known fluid catalytic cracking catalyst (general CVZ series fluid catalytic catalysts provided by JGC Catalysts and Chemicals Co., Ltd.) can be used.
[0051] <Metal Scavenger> The fluid catalytic cracking catalyst composition of the present invention preferably contains the metal trap of the present invention in the range of 0.5 to 10 mass %. If the metal trap is less than 0.5 mass %, the effect of trapping metals such as vanadium and nickel to suppress poisoning of the fluid catalytic cracking catalyst may not be sufficient, which is not preferable. On the other hand, if the metal trap exceeds 10 mass %, the zeolite ratio in the fluid catalytic cracking catalyst composition decreases, which has a negative effect on the catalytic activity, and the excess active metal component is also a factor of adverse effects on the activity, such as poisoning of the zeolite, which is not preferable.
[0052] <Specific surface area (SA)> The fluid catalytic cracking catalyst composition according to the present invention has a specific surface area (SA) of 30 to 150 m as measured by the BET (Brunauer-Emmett-Teller) method. 2 / g. The specific surface area is preferably in the range of 30 m 2 If the contact time is less than 150 m / g, the catalytic cracking reaction may not proceed sufficiently in a short contact time in a fluid catalytic cracking process or the like. 2 If it is more than 1 / g, there is a risk that sufficient strength cannot be obtained as a fluid catalytic cracking catalyst.
[0053] <Average particle size of metal scavenger and fluid catalytic cracking catalyst composition> The average particle size of the fluid catalytic cracking catalyst composition according to the present invention is preferably 40 to 100 μm, and more preferably 50 to 90 μm. The average particle size of the metal capture agent and the fluid catalytic cracking catalyst composition can be measured by preparing samples for measuring particle size distribution, and using a laser diffraction / scattering particle size distribution analyzer (LA-950V2) manufactured by Horiba, Ltd. Specifically, the sample is placed in a solvent (water) so that the light transmittance is in the range of 70 to 95%, and the measurement is performed at a circulation speed of 2.8 L / min, ultrasonic waves for 3 min, and the number of repetitions is 30. The median diameter (D50) is adopted as the average particle size.
[0054] <Pore volume (PV)> The fluid catalytic cracking catalyst composition according to the present invention has a pore volume (PV) of 0.05 to 0.50 ml / g, preferably 0.10 to 0.45 ml / g, over the entire pore diameter range, as measured by a water pore filling method. When the fluid catalytic cracking catalyst composition is used as a fluid catalyst, if the pore volume is less than 0.05 ml / g, sufficient catalytic cracking activity may not be obtained. On the other hand, if the pore volume is more than 0.50 ml / g, the strength of the fluid catalytic cracking catalyst composition may be reduced.
[0055] <Bulk density (ABD)> The bulk density (ABD) of the fluid catalytic cracking catalyst composition according to the present invention is preferably set to a lower limit of 0.70 g / ml. If the bulk density is lower than 0.70 g / ml, the abrasion resistance is insufficient, and when used as a fluid catalyst, it may easily become powdered, which may cause the components of the fluid catalytic cracking catalyst composition to scatter. The bulk density (ABD) of the fluid catalytic cracking catalyst composition was measured by using a 25 ml cylinder to measure the weight of the metal capture agent and calculating the bulk density from the weight per unit volume.
[0056] <Loss on ignition (LOI)> The loss on ignition (LOI) of the fluid catalytic cracking catalyst composition according to the present invention is preferably in the range of 20% to 35%, and more preferably in the range of 22 to 30%. The loss on ignition (LOI) was measured by measuring the weight loss amount when the composition was kept in an electric furnace at 1000°C for 1 hour, and calculating the weight loss rate to obtain the loss on ignition (LOI). EXAMPLES
[0057] [MTR-1] Preparation of metal trap MTR-1 (metal trap using silica particles with an average particle size of 4-5 nm and pseudoboehmite) Crystalline boehmite with a solid content of 84.2% by mass (specific surface area of 105 m 2 / g) 23.8 g, and magnesium oxide (specific surface area 27 m) with a solid content of 97.0 mass% 241.2 g of calcium carbonate (calcium oxide equivalent) and 34.8 g of calcium carbonate with a solid content of 43.1% by mass (calcium oxide equivalent) were mixed with 230.4 g of ion-exchanged water, and 124.2 g of silica sol with a solid content of 20.1% by mass and a particle size of 4-5 nm was added and stirred to obtain a mixed slurry. The pH of the mixed slurry at this time was 10.2.
[0058] The obtained mixed slurry was made into droplets and spray-dried in a spray dryer with an inlet temperature of 240°C and an outlet temperature of 150°C to obtain spray-dried particles (metal capture agent) with an average particle size of 75 μm. The obtained spray-dried particles (metal capture agent) were suspended in ion-exchanged water to a solid content concentration of 10 mass%, to obtain a suspension slurry. The pH of the suspension slurry at this time was 10.5. The suspension slurry was filtered and further washed with ion-exchanged water in an amount 15 times the amount of the solid content to obtain a washed slurry. The washed slurry was dehydrated to obtain a spray-dried particle washed cake.
[0059] The resulting spray-dried, washed cake was transferred to a pad and placed in a fan-type box dryer where it was heated to 120°C over 2 hours at a rate of 2°C / min, and then held at 120°C for 8 hours to obtain MTR-1. The resulting MTR-1 had a loss on ignition (LOI) of 29.5% and a specific surface area of 210 m2 measured after being held at 600°C for 2 hours. 2 / g, and the abrasion resistance index (CAI) was 3. EXAMPLES
[0060] [MTR-2] Preparation of metal trap MTR-2 (metal trap prepared by increasing the pH of the mixed slurry) A metal capture agent MTR-2 was obtained in the same manner as in the preparation of MTR-1, except that an aqueous sodium hydroxide solution was added to the prepared slurry to adjust the pH to 11.0. Specifically, spray drying was carried out in the same manner as in the preparation of MTR-1, and the slurry was suspended in ion-exchanged water to a solids concentration of 10 mass % to obtain a suspension slurry. The pH of the suspension slurry at this time was adjusted to 10.9. The loss on ignition (LOI) of the obtained MTR-2 was 24.6%, and the specific surface area measured after holding at 600°C for 2 hours was 163 m 2 / g, and the abrasion resistance index (CAI) was 3. EXAMPLES
[0061] [MTR-3] Preparation of metal trap MTR-3 (metal trap prepared by increasing the pH of the cleaning slurry) Metal capture agent MTR-3 was obtained in the same manner as MTR-1, except that when the spray-dried product was suspended in ion-exchanged water, an aqueous sodium hydroxide solution was added to adjust the pH of the suspension slurry to 11.3. The loss on ignition (LOI) of the obtained MTR-3 was 30.8%, and the specific surface area measured after holding at 600°C for 2 hours was 226 m 2 / g, and the abrasion resistance index (CAI) was 2. EXAMPLES
[0062] [MTR-4] Preparation of metal trap MTR-4 (metal trap prepared by increasing the pH of the mixed slurry and using a dry spray) The resulting spray-dried, washed cake was fed from the top of a spray dryer with an inlet temperature of 240°C and dried with hot air in the same manner as in the preparation of MTR-2 to obtain a metal scavenger, MTR-4. The loss on ignition (LOI) of the resulting MTR-4 was 20.8%, and the specific surface area measured after holding at 600°C for 2 hours was 140 m. 2 / g, and the abrasion resistance index (CAI) was 6. EXAMPLES
[0063] [MTR-5] Preparation of metal trap MTR-5 (metal trap prepared by increasing the pH of the washing slurry and using a drying spray) The resulting spray-dried, washed cake was fed from the top of a spray dryer with an inlet temperature of 240°C and dried with hot air in the same manner as in the preparation of MTR-3, to obtain a metal scavenger, MTR-5. The resulting MTR-4 had a loss on ignition (LOI) of 25.6% and a specific surface area of 188 m2 measured after being held at 600°C for 2 hours. 2 The abrasion resistance index (CAI) was 5.
[0064] [MTR-R1] Preparation of metal scavenger MTR-R1 The dehydrated cake was fed from the top of a spray dryer with an inlet temperature of 240°C and dried with hot air in the same manner as in the preparation of MTR-1 to obtain a metal capture agent MTR-R1. The loss on ignition (LOI) of the obtained MTR-R1 was 17.8%, and the specific surface area measured after holding at 600°C for 2 hours was 125 m. 2 The abrasion resistance index (CAI) was 12.
[0065] [MTR-R2] Preparation of metal scavenger MTR-R2 An attempt was made to produce a metal capture agent MTR-R2 in the same manner as in the preparation of MTR-1, except that nitric acid was added to the prepared slurry to adjust the pH to 9.0. However, the viscosity of the prepared slurry increased too much, making it impossible to carry out spray drying, and therefore the metal capture agent MTR-R2 could not be produced.
[0066] [MTR-R3] Preparation of metal scavenger MTR-R3 When suspending the spray-dried product in ion-exchanged water, an aqueous nitric acid solution was added to adjust the pH to 6.5, and after filtering, the product was washed with ion-exchanged water in an amount 15 times the solid content, and then dehydrated to obtain a washed cake of spray-dried particles. The metal capture agent MTR-R3 was obtained in the same manner as in the preparation of MTR-1, except that the washed cake of spray-dried particles obtained was fed from the top of a spray dryer with an inlet temperature of 240°C and dried with hot air. The loss on ignition (LOI) of the obtained MTR-R3 was 16.8%, and the specific surface area measured after holding at 600°C for 2 hours was 110 m. 2 / g, and the abrasion resistance index (CAI) was 14.
[0067] The attrition resistance of the metal traps MTR-1 to MTR-5, MTR-R1, and MTR-R3 prepared above was evaluated by the attrition resistance index (CAI) measured by the method described in Catalysts and Chemical Engineering Reports, Vol. 13, No. 1, p. 65, 1996. The sample conditions and performance measurement results of the metal traps are shown in Table 1.
[0068] [Table 1]
[0069] [Attrition resistance evaluation results for metal traps] As shown in Table 1, the metal capture agents MTR-1 to 5 of the invention have a wear resistance index (CAI) in the range of 0.1 to 10, and thus have sufficient wear resistance. On the other hand, MTR-R1 and R3 have a wear resistance index (CAI) of more than 10.
[0070] [Performance evaluation of fluid catalytic cracking catalyst composition containing metal scavenger] In order to confirm the effect of adding the metal capture agent according to the present invention, 5 mass% of the metal capture agents MTR-1 and 2 prepared above were added to a general CVZ series fluid catalytic cracking catalyst provided by JGC Catalysts and Chemicals Co., Ltd. to obtain a fluid catalytic cracking catalyst composition for performance evaluation.
[0071] For a fluid catalytic cracking catalyst composition using a silica binder, The metal traps MTR-1 to MTR-5 produced above were blended at a mass ratio of 5% to prepare a fluid catalytic cracking catalyst for evaluation, and performance evaluation was performed. The fluid catalytic cracking catalyst used contained 17 mass% silica binder, 30 mass% zeolite, 20 mass% activated alumina, 33 mass% kaolin, and 5 mass% of the above metal traps, and had a specific surface area of 275 m. 2 / g, and the pore volume is 0.30 ml / g.
[0072] <Preparation of fluid catalytic cracking catalyst composition containing metal scavenger> A catalyst composition is obtained by mixing the fluid contact catalyst CVZ manufactured by JGC Catalysts and Chemicals Co., Ltd. and the metal capture agent of the present invention in a ratio of 95:5.
[0073] [Catalyst performance evaluation test] Fluid catalytic cracking catalyst compositions were prepared by blending each metal capture agent with the fluid catalytic cracking catalyst obtained as described above, and the performance evaluation test of the catalyst composition was performed using the same crude oil and the same reaction conditions using ACE-MAT (Advanced Cracking Evaluation-Micro Activity Test). The results of the performance evaluation test of each catalyst composition are shown in Table 2. Each yield was expressed as mass % based on the mass of each product when C / O = 5.0.
[0074] However, before conducting these performance evaluation tests, nickel and vanadium were deposited on the surface of each catalyst in advance at 1000 ppm by mass (the mass of nickel divided by the mass of the catalyst) and 2000 ppm by mass (the mass of vanadium divided by the mass of the catalyst), respectively, and then steamed to perform pseudo-equilibrium treatment. Specifically, each catalyst was calcined at 600°C for 2 hours, and then absorbed in a toluene solution of a predetermined amount of nickel naphthenate and vanadium naphthenate, and then dried at 110°C, calcined at 600°C for 1.5 hours, and then steamed at 780°C for 13 hours.
[0075] The operating conditions in the performance evaluation test were as follows: Feedstock: Desulfurized atmospheric residue (DSAR) of crude oil + desulfurized vacuum gas oil (DSVGO) (50+50) Catalyst / oil mass ratio (C / O): 5.0 Reaction temperature: 520℃ 1) Conversion rate=100-(LCO+HCO+CLO) (mass%) 2) Yield: The mass of each product when C / O=5.0 was expressed as mass %. 3) Boiling point range of gasoline: 30~216℃ (Gasoline) 4) Boiling point range of LCO: 216~343℃ (LCO: Light Cycle Oil) 5) Boiling point range of HCO and CLO: 343℃+ (HCO: Heavy Cycle Oil, CLO: Clarified Oil) 6) LPG (Liquefied Petroleum Gas) 7) Dry Gas: Methane, Ethane and Ethylene
[0076] [Table 2]
[0077] [Catalyst composition activity evaluation results] According to the activity evaluation results of the catalyst composition (Table 2), the performance evaluation results (yield: C / O=5.0) of the catalyst (invention example) containing 5.0 mass% of the metal traps MTR-1 to MTR5 prepared in Example 1 clearly show a decrease in the yield of H2, dry gas, and coke, and an increase in the gasoline yield, compared to the case of 100% of the base catalyst containing no metal traps (Test No. 1: Reference). In addition, the catalyst composition (Test No. 7) to which 15.0 mass% of the metal trap MTR-3 was added showed a higher improvement in the yield of H2, coke, and dry gas than the catalyst to which 5.0 mass% of the metal trap MTR-3 was added, but the conversion rate was lower. In addition, when 0.3 mass% of MTR-3 was added (Test No. 8), no clear improvement was observed in any of the yields. [Industrial Applicability]
[0078] As explained above, the metal capture agent according to the present invention has high metal capture ability and wear resistance, and is therefore suitable for use in the cracking of hydrocarbon oils containing nickel and vanadium by adding it to a fluid catalytic cracking catalyst, which can stably maintain the function of the catalyst for a long period of time. In the above example, a fluid catalytic cracking catalyst using an alumina binder is used, but other binders and other additives can also be suitably combined. Thus, the present invention is extremely useful for fluid catalytic cracking for residual oil processing, and can be used in industries such as oil refining and the petrochemical industry.
Claims
1. A composition comprising: 15 to 35 mass% silicon oxide (silica-based) calculated as oxide (SiO 2 ); 10 to 30 mass% alumina component calculated as oxide (Al 2 O 3 ); and a metal component including magnesium; The average particle size is 40 to 100 μm, The specific surface area is 140 to 250 m 2 / g; The pore volume is 0.05 to 0.50 ml / g; A metal scavenger having a loss on ignition (LOI) of 20-35%.
2. 2. The metal capture agent according to claim 1, wherein the metal capture agent has an abrasion resistance index (CAI) in the range of 2.0 to 10.
3. a first step of adding an alumina component or an alumina component precursor to a silicon oxide (silica-based) binder, and further mixing with a magnesium compound having a specific surface area of 20 to 40 m 2 / g to obtain a mixed slurry, and then heating the mixed slurry to obtain a metal capture agent precursor; a second step of drying the metal capture agent precursor to obtain spray-dried particles; a third step of washing the spray-dried particles to obtain a washed spray-dried particle cake; and a fourth step of heat treating the spray-dried washed cake to obtain a metal capture agent. The method for producing a metal capture agent, wherein in the heat treatment of the washed cake of spray-dried particles, the drying temperature of the washed cake of spray-dried particles is 80 to 200°C, and the heating rate is 2.0 to 10.0°C / min.
4. A fluid catalytic cracking catalyst composition comprising the metal capture agent of claim 1 and a fluid catalytic cracking catalyst.
Citation Information
Patent Citations
Composition for passivating vanadium in catalytic cracking and its manufacture
JP1996504397A
Improved Heavy Metal Capture Aid for FCC Processes
JP2013506548A
Phosphorus collection material and automotive exhaust gas purification catalyst using the same
JP2015188881A
Porous molding
JP2019118879A
Metal scavenger, method for manufacturing metal scavenger, and fluid catalytic cracking catalyst
WO2020129455A1